A Participatory Action Research-Based Community Development Program to Overcome Problem of Access to Fresh Water: Case Study of Malingping Village, West Bandung - Pangestu, Aria Bayu; Wisesa, Anggara; Putranto, Nur Arief Rahmatsyah (The Asian Journal of Technology Management (AJTM), 2018)
Abstract. Water connects every aspect of life, but access to it still becomes a problem for some communities in the world. Many initiatives in the form of community development program have been developed to help people to get better access to fresh water. To accomplish this, it needs several steps to be done. It starts with the needs identification and ends with the program implementation. However, the question is whether the identified needs is the priority and whether the program recipient needs it. This condition causes that not few community programs end ineffectively. The community development program is not only about the program, but the term explains the overall process. This paper is to explore how Participatory Action Research can be a method to increase the efficiency of the community development program by taking a case of community development program run by students of a business school in Indonesia. By using the Participatory Action Research method, the students identified problems faced by the community and worked collaboratively with them to solve the problem. As a result, they built a freshwater facility that can be used by all of the people in the community, and now they have better access to water, so they no longer have difficulty in getting fresh water especially in the dry season. With this new freshwater facility that is owned and managed communally, people have enough water supply to fulfill their needs as well as to support their activities such as make irrigation that eventually can increase their wellness.Â Keywords: Access to fresh water, community development, collaborative action, participatory action research,Â sustainability.